SMS GATEWAY SYSTEM NOTIFICATION OF FOREIGNERS' RESIDENCE PERMITS AT CLASS II NON-TPI IMMIGRATION OFFICES IN DEPOK - Catur Susaningsih; Priati Assiroj; Fadhil Atallah Dwiputro (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The Immigration Office Class II Non-TPI Depok is an Immigration Technical Implementation Unit that has a fairly wide work area coverage. This is certainly a challenge for the Depok Immigration Office in carrying out supervision and services for foreigners living in its working area. The increasing use of cellular telephones in the world must be utilized by the Depok Immigration Office in using cellular telephones to carry out supervision and service to foreigners living in its working area. One system that can take advantage of the use of cellular phones is the SMS Gateway system which can be used as a notification system to foreigners regarding the validity period of their residence permit. The purpose of this study is to determine the extent to which the SMS Gateway system for notification of foreigners' residence permits is useful and important at the Depok Immigration Office, as well as explaining how it is implemented. In making the system, the author uses a system development method, namely the System Development Life Cycle which aims to make the system can be made with clear stages and the system can be made well. The results of this study are the SMS Gateway system for foreigner notification which is used as a reminder of the validity period of the foreigner's residence permit.